Aktualisasi Sufisme dan Masa Depan Pendidikan Islam Modern Era Society 5.0 - Adibah, Ida Zahara; Chasanah, Uswatun (Universitas Islam Sultan Agung, 2023)
Education always develops following the dynamics of people's lives, Islamic education is faced with big challenges after the industrial revolution 4.0 era, then